Republic of Kosovo : Technical Assistance Report- Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper assesses public investment in the Republic of Kosovo. Public investment levels in Kosovo have exceeded comparator counties' over the last four years, partially owing to the need to build up its relatively low level of capital stock. Despite the high level of spending, the efficiency of Kosovo's public investment is relatively low. Most of Kosovo's public investment institutions are of good or medium strength on paper, but much weaker in their practical implementation. Planning institutions for investment are comprehensive but not fully effective. Systems for allocating funds for capital investment are assessed good or medium, with some implementation gaps.